Comunicação, corpo e territorialidades: o declínio das narrativas globalistas - Alencar, Jakson Ferreira de (2016)
The thesis identifies and analyzes the decline of globalists narratives, in connection with the communication, which does not abolish the corporeity and territorialities, as suggested theories that predicted the global homogeneity; does not dependent of them and of the complexity that arise from them, even when using the most advanced technologies and the most international media. Parts of the world become more visible, as well as divergences, disparity and differences. Two thirds of humanity are not part of the imagined full connection, and there remains very muting, incommunication, superficial knowledge or ignorance of various shapes and large parts of the word, even for those superconnected. The acceleration of cultural exchanges, increasing the amount of information circulating, of media and of channels, although spreading equal products and information, have produced unpredictable and unexpected results. Instead of generating the homogeneity, is increasing diversification, segmentation, fragmentation, resistances and even intolerances. Maintaining and creating new and multiple territorialities, even in the context of digital networks and more advanced communication technologies. To identify the decline of globalism, the thesis is based on authors such as Wolton (2006), Ghemawat (2012), Milton Santos (2000, 2006, 2008), Martín-Barbero (2009, 2012), Walden Bello (2003), Kellner (2001), Pieterse (2009), Martel (2012), Vergopoulos (2005), Haesbaert (2004, 2005) and Castells (1999), among others. Search the body's relation with the communication with the bodymedia theory (Katz e Greiner, 2004, 2005, 2010, 2014), and to treat the communication relation with the environment, the space and the culture employs Pinheiro (2009, 2013), Warnier (2003) and Dênis Moraes (2009, 2013), among others. With them formulates a critical reading of a empirical corpus which shows the rise of these trends, composed of the information published by the agencies at the period after the onset of the economic crisis of 2008 up until the end of 2012. The goal is to demonstrate that global levels of integration are still very low, far from suggests the theses of the “global village”. The hypothesis is that the communication technologies and the ease of transmission and access to information seem to interconnect and homogenize the world, but may not be creating communication, mutual understanding, common views, understanding, integration and the expected homogeneity